TINJAUAN SISTEMATIS PENERAPAN SISTEM INFORMASI MANAJEMEN OPERASIONAL: ANALISIS LITERATUR MENGGUNAKAN PENDEKATAN PRISMA PADA ARTIKEL TERINDEKS SINTA TAHUN 2020–2025 - Itrizal Itrizal; Vicky Brama Kumbara (Ensiklopedia of Journal, 2026)
Operational Management Information Systems (MIS) have become an essential enabler for organizations across sectors—spanning manufacturing, financial services, retail, and healthcare—by strengthening business-process efficiency, data reliability, and the pace of decision-making. This review sets out to chart the trends, characteristics, and principal findings reported in Indonesian scholarly literature on Operational MIS adoption, drawing on SINTA-indexed journals published between 2020 and 2025. A Systematic Literature Review (SLR) design was adopted, guided by the 2020 Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Literature was traced through Google Scholar, Garuda, and the SINTA portal using the combined search terms "management information system," "operational management," and "operational efficiency." Following identification, screening, and eligibility review, eighteen articles satisfied the inclusion criteria and were examined in depth. Findings show that Operational MIS adoption is repeatedly linked to lower operating costs, quicker information flow, more reliable data, and improved managerial decision-making. The review further points to recurring obstacles—human-resource readiness, weak cross-system integration, and constrained technological infrastructure—especially within mid-sized organizations and healthcare facilities. It closes by calling for quantitative empirical studies covering a wider range of sectors and assessing the long-term impact of Operational MIS implementation.Keywords: management information system, operational management, operational efficiency, systematic review, PRISMA